Development of Education for Indigenous Minorities in Alaska - Gmerek, Tomasz (Biuletyn Historii Wychowania, 2018)
The history of development and modern forms of functioning of education for indigenous minorities in Alaska reveal trends which appeared in other areas of the Arctic. The systematic activity of education, along with the influence of other state institutions (military, offices), and also the often destructive influence of religious organizations contributed to irreversible changes in the ethnic awareness of indigenous communities. They have resulted in permanent changes in the ethnic identity of peoples inhabiting the Arctic for thousands of years. Initially, education was used by churches in the process of Christianization. Then, education was used to indoctrinate state ideologies (in particular national ones). And although currently various ethnic and national groups in the areas of the High North have opportunities in the sphere of using their own language and protecting their identity, the criteria for social promotion through the education system have remained unchanged. As a consequence, even representatives of large ethnic groups are determined – in their education and life choices. Nowadays, the drama of indigenous minorities living in Alaska and other minorities in the polar regions continues, and we cannot expect it to end in a “constructive” manner. The dilemma of “preserving identity” in the conditions of a multi-ethnic society does not lose its focus. Individuals from indigenous communities usually have to choose between achieving educational and socio-professional success (as part of the dominant majority system) and the attachment to their traditional culture.